A Systematic Literature Review: Digital Leadership of Millennial Kiai in The Era of Digitalization in Islamic Boarding Schools - Nailul Farah, Nabilah; Imron, Ali; Budi Wiyono, Bambang (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The digitalization era brings significant changes in various aspects of life, including the world of pesantren (Islamic boarding schools). Millennial Kiai (Islamic leaders) play a crucial role in guiding pesantren into the digital era. This article aims to discuss digital leadership among millennial Kiai in addressing the challenges of digitalization. The research adopts a qualitative approach with a systematic literature review using the PRISMA method. The literature review process took place from February 2024 to March 2024, utilizing Google Scholar as the primary database. The research findings indicate that digital leadership among millennial Kiai entails possessing long-term vision, creativity, and the ability to lead change and confront the challenges of the digital era, along with strategies and challenges in facing them. The article concludes that digital leadership among millennial Kiai represents an integration of traditional values with digital technology in efforts to realize transformation and progress within religious institutions or communities.